Seed germination traits of Ailanthus altissima, Phytolacca americana and Robinia pseudoacacia in response to different thermal and light requirements. Issue 4 (3rd August 2020) - Pepe, Maria; Gratani, Loretta; Fabrini, Giuseppe; Varone, Laura
Abstract: Invasion of alien plant species (IAS) represents a serious environmental problem, particularly in Europe, where it mainly pertains to urban areas. Seed germination traits contribute to clarification of invasion dynamics. The objective of this research was to analyze how different light conditions (i.e., 12‐hr light/12‐hr darkness and continuous darkness) and temperature regimes (i.e., 15/6°C, 20/10°C and 30/20°C) trigger seed germination of Ailanthus altissima (AA), Phytolacca americana (PA) and Robinia pseudoacacia (RP). The relationship between seed germination and seed morphometric traits was also analyzed. Our findings highlight that temperature rather than light was the main environmental factor affecting germination. RP germinated at all tested temperatures, whereas at 15/6°C seeds of AA and PA showed physiological dormancy. RP had a higher germination capacity at a lower temperature, unlike AA and PA, which performed better at the highest temperatures. Light had a minor role in seed germination of the three species. Light promoted germination only for seeds of PA, and final germination percentage was 1.5‐fold higher in light than in continuous darkness. Seed morphometric traits (thickness [T], area [A] and volume [V]) had a significant role in explaining germination trait variations. The results highlight the importance of increasing our knowledge on seed germination requirements to predict future invasiveness trends. The increase in global temperature could further advantage AA and PA in terms of germinated seeds, as well as RP by enhancing the germination velocity, therefore compensating for a lower germination percentage of this species at the highest temperatures. Abstract : Robinia pseudoacacia (RP) germinated at all tested temperatures, whereas at 15/6 °C seeds of Ailanthus altissima (AA) and Phytolacca americana (PA) showed physiological dormancy. RP had a higher germination capacity at a lower temperature, unlike AA and PA, which performed better at the highest temperatures.